Reference materials for DNA-based diagnostics testing; principles, comparative analysis, contemporary applications, and future recommendation in Indonesia - Nanda Diva Meilani, Jekmal Malau, Anastasia Aliesa Hermosaningtyas,, Aliya Azkia Zahra, Ahsanal Kasasiah, Ratika Rahmasari, Agatha Nabilla Lestari, Muhareva Raekiansyah (Journal of Applied Pharmaceutical Science, 2025)
Diagnostic testing is crucial in modern healthcare, providing essential health information and influencing clinical decisions and patient outcomes. Ensuring the validity and quality of these tests is vital, with stringent quality control and assurance procedures enforced by regulatory bodies and healthcare facilities. Reference materials (RMs) are essential for the accuracy and reliability of DNA-based diagnostic tests, serving as benchmarks for error detection, test validity, and consistency. This study reviews the necessity of effective control substances for precise diagnostic testing through a narrative literature review of synthetic DNA sequences, recombinant plasmids, genomic DNA, and cell lines as RMs, sourced from PubMed, Scopus, and Google Scholar over the last decade. Each RM type has specific advantages and disadvantages impacting diagnostic performance: gBlocks are highly specific but lack genomic complexity; recombinant plasmids offer flexibility but face stability and contamination issues; genomic DNA provides comprehensive diagnostic information but is complex and costly; cell lines simulate in vivo conditions well but are prone to genetic drift and contamination. The review emphasizes the critical role of RMs in DNA-based diagnostics and highlights challenges faced by Indonesian laboratories, recommending national coordination and international collaboration to enhance RMs’ availability, thereby improving patient outcomes and aligning with global standards.
Keywords: Reference materials, DNA-based diagnostic testing, gBlocks, recombinant plasmids, genomic DNA, cell lines